Negative electrode for lithium secondary battery and lithium secondary battery comprising same
By using a specific combination of silicon -based activated materials, conductive materials and adhesives in the negative electrode of lithium secondary batteries, and control the conductivity, solve the solution of silicon active materials in the volume expansion of the lithium secondary battery caused The problem achieves lithium secondary battery performance of high -capacity and long life.
Patent Information
- Application Number
- CN202380050443.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-12-26
- Filing Date
- 2023-12-13
- Publication Date
- 2025-01-24
AI Technical Summary
When using silicon-based active material as the negative electrode of lithium secondary battery, volume expansion leads to disconnection of conductive paths, reducing battery performance, and the non-conductivity of silicon-based materials requires the addition of conductive material or surface treatment to improve the conductivity.
By using a specific combination of a silicon-based active material, a conductive material, and a binder in the negative electrode of a lithium secondary battery and improving its dispersion, the conductivity of the negative electrode is controlled to be 1 S/cm2 or more and 3,000 S/cm2 or less. within the range to maintain the performance of silicon-based active materials.
When using silicon -based activated materials to manufacture high -capacity lithium secondary batteries, maintain the conductivity and performance, avoid volume expansion damage to the guide circuit, and improve the output characteristics and life of the battery.
Smart Images

Figure CN119365994A_ABST
Abstract
Description
Technical Field
[0001] This application claims the benefit of priority from Korean Patent Application No. 10-2022-0184220 filed in the Korean Intellectual Property Office on December 26, 2022, the entire contents of which are incorporated herein by reference.
[0002] The present application relates to a negative electrode for a lithium secondary battery and a lithium secondary battery including the negative electrode. Background Art
[0003] As a part of the increasing demand for the use of alternative or clean energy due to the rapid increase in the use of fossil fuels, the field of power generation and storage using electrochemical reactions is being most actively researched.
[0004] Currently, secondary batteries are a representative example of electrochemical devices utilizing such electrochemical energy, and the scope of use thereof tends to gradually expand.
[0005] With the technological development and demand increase of mobile devices, the demand for secondary batteries as energy sources has increased dramatically. Among such secondary batteries, lithium secondary batteries with high energy density and voltage, long cycle life and low self-discharge rate have been commercialized and widely used. In addition, methods for preparing high-density electrodes with higher energy density per unit volume as electrodes of such high-capacity lithium secondary batteries have been actively studied.
[0006] Generally, a secondary battery includes a positive electrode, a negative electrode, an electrolyte, and a separator. The negative electrode includes a negative electrode active material for intercalating and deintercalating lithium ions from the positive electrode, and silicon-based particles having a high discharge capacity can be used as the negative electrode active material.
[0007] In particular, in accordance with the demand for high energy density batteries in recent years, a method of increasing capacity by using a silicon-based compound (such as Si / C or SiOx) having a capacity 10 times or more higher than that of a graphite-based material as a negative electrode active material has been actively studied. However, when compared with the commonly used graphite, the silicon-based compound as a high-capacity material has a large capacity, but undergoes rapid volume expansion during the charging process, thereby disconnecting the conductive path and reducing battery characteristics.
[0008] Therefore, in order to solve the problems that occur when a silicon-based compound is used as a negative electrode active material, methods for suppressing volume expansion itself, such as a method of controlling a driving potential, a method of further coating a thin film on an active material layer, and a method of controlling the particle size of a silicon-based compound, or various methods for preventing disconnection of a conductive path have been discussed. However, the above methods may instead reduce the performance of the battery, and thus their application is limited, and thus there are still limitations in commercializing the manufacture of batteries including negative electrodes having a high content of silicon-based compounds.
[0009] In addition, in the case of a carbon-based negative electrode such as conventional graphite, regarding the active material, since graphite itself is a material with high conductivity, the conductivity range does not have much meaning. However, when a silicon-based active material is used to enhance capacity characteristics, the silicon-based active material is a non-conductive material, so conductivity should be imparted by adding a negative electrode conductive material or surface treating the silicon-based active material.
[0010] Therefore, it is necessary to study a negative electrode composition that can prevent volume expansion, damage to the conductive path and surface fracture caused by charging and discharging during the manufacture of a silicon-based negative electrode for maximizing capacity characteristics, and to study a negative electrode that can maintain conductivity in a silicon-based negative electrode.
[0011] Prior art literature
[0012] (Patent Document 1) Japanese Patent Application Publication No. 2009-080971 Summary of the invention
[0013] Technical issues
[0014] For the negative electrode using the silicon-based active material, it was found that while maintaining the conductive network of the electrode, the negative electrode conductivity should be maintained within a certain range so that the performance of the silicon-based active material (which is a non-conductive material) can be maintained. In other words, it was found that when a specific combination of the silicon-based active material, the conductive material and the binder contained in the silicon-based negative electrode is adopted and its dispersibility is improved, a certain conductivity can be maintained.
[0015] Therefore, the present application attempts to provide a negative electrode for a lithium secondary battery, and a lithium secondary battery including the negative electrode.
[0016] Technical Solution
[0017] An exemplary embodiment of the present specification provides a negative electrode for a lithium secondary battery, comprising: a negative electrode collector layer; and a negative electrode active material layer, the negative electrode active material layer comprising a negative electrode active material layer composition and disposed on one surface or both surfaces of the negative electrode collector layer, wherein the negative electrode active material layer composition comprises a silicon-based active material, wherein the negative electrode active material layer has a porosity of 10% to 50%, and wherein the conductivity of the negative electrode for a lithium secondary battery satisfies 1 S / cm 2 Above and 3,000 S / cm 2 The following range.
[0018] Another exemplary embodiment provides a lithium secondary battery including: a positive electrode; a negative electrode for a lithium secondary battery according to the present application; a separator disposed between the positive electrode and the negative electrode; and an electrolyte.
[0019] Beneficial Effects
[0020] The negative electrode for a lithium secondary battery according to an exemplary embodiment of the present invention has an inferred conductivity range in which the performance of the silicon-based active material as a non-conductive material can be maintained when the silicon-based active material as a high-capacity material is used to manufacture a high-capacity battery.
[0021] That is, in conventional carbon-based negative electrodes, the conductivity of the negative electrode itself is not an important factor because graphite itself has high conductivity. However, in negative electrodes that use silicon-based active materials to achieve fast charging and high energy density, non-conductive material silicon is used as described above. In this case, the rolled porosity of the negative electrode itself and the degree of dispersion of the conductive material are very important. According to the present application, the conductivity of the negative electrode is controlled to 1 S / cm by adjusting the corresponding factors. 2 Above and 3,000 S / cm 2 The following range is achieved, thereby ensuring and maintaining the performance of the silicon-based active material. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 is a view showing a stack structure of a negative electrode for a lithium secondary battery according to an exemplary embodiment of the present application.
[0023] Figure 2 is a view showing a stack structure of a negative electrode for a lithium secondary battery according to an exemplary embodiment of the present application.
[0024] Figure 3 is a view showing a stack structure of a lithium secondary battery according to an exemplary embodiment of the present application.
[0025] <Reference Numbers>
[0026] 10: Negative electrode collector layer
[0027] 20: Negative electrode active material layer
[0028] 30: Diaphragm
[0029] 40: Positive electrode active material layer
[0030] 50: Positive electrode collector layer
[0031] 100: Negative electrode for lithium secondary battery
[0032] 200: Positive electrode for lithium secondary battery DETAILED DESCRIPTION
[0033] Before describing the present invention, some terms are first defined.
[0034] In the present specification, when a part “includes,” “contains,” or “has” a constituent element, unless otherwise specifically described, this does not mean that another constituent element is excluded but means that another constituent element may be further included.
[0035] In this specification, “p to q” means a range of “p or more and q or less”.
[0036] In this specification, the "specific surface area" is measured by the BET method, and specifically, is calculated based on the nitrogen adsorption amount at liquid nitrogen temperature (77 K) by using BELSORP-mini II available from BEL Japan, Inc. That is, in this application, the BET specific surface area may refer to the specific surface area measured by the above-mentioned measurement method.
[0037] In this specification, "Dn" refers to particle size distribution, and refers to the particle size at n% point in the cumulative distribution of the number of particles according to the particle size. That is, D50 is the particle size (average particle size) at 50% point in the cumulative distribution of the number of particles according to the particle size, D90 is the particle size at 90% point in the cumulative distribution of the number of particles according to the particle size, and D10 is the particle size at 10% point in the cumulative distribution of the number of particles according to the particle size. On the other hand, the particle size distribution can be measured using a laser diffraction method. Specifically, after the powder to be measured is dispersed in a dispersion medium, the resulting dispersion is introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac S3500), in which, when the particles pass through a laser beam, the difference in the diffraction pattern according to the particle size is measured, and then the particle size distribution is calculated.
[0038] In the present specification, the description "a polymer comprises a certain monomer as a monomer unit" means that the monomer participates in a polymerization reaction and is contained in the polymer as a repeating unit. In the present specification, when a polymer comprises a monomer, this is interpreted as the same as: a polymer comprises a monomer as a monomer unit.
[0039] In this specification, it is understood that the term "polymer" is used in a broad sense, including copolymers, unless otherwise specified as a "homopolymer".
[0040] In this specification, the weight average molecular weight (Mw) and the number average molecular weight (Mn) are polystyrene conversion molecular weights measured by gel permeation chromatography (GPC) while using commercially available monodisperse polystyrene polymers (standard samples) with various polymerization degrees for measuring molecular weight as standard materials. In this specification, unless otherwise specifically described, molecular weight refers to weight average molecular weight.
[0041] Hereinafter, embodiments of the present invention will be described in detail with reference to the accompanying drawings so that those skilled in the art can easily implement the present invention. However, the present invention can be implemented in various forms and is not limited to the following description.
[0042] An exemplary embodiment of the present specification provides a negative electrode for a lithium secondary battery, comprising: a negative electrode collector layer; and a negative electrode active material layer, the negative electrode active material layer comprising a negative electrode active material layer composition and disposed on one surface or both surfaces of the negative electrode collector layer, wherein the negative electrode active material layer composition comprises a silicon-based active material, wherein the negative electrode active material layer has a porosity of 10% to 50%, and wherein the conductivity of the negative electrode for a lithium secondary battery satisfies 1 S / cm 2 Above and 3,000 S / cm 2 The following range.
[0043] The conductivity of the negative electrode for the lithium secondary battery according to the present application can meet 1 S / cm 2 Above and 3,000 S / cm 2 Below, preferably 10 S / cm 2 Above and 2,900 S / cm 2 Below, more preferably 100 S / cm 2 Above and 2,800 S / cm 2 The following range.
[0044] The negative electrode for a lithium secondary battery according to an exemplary embodiment of the present invention has a derived conductivity range within which, when a silicon-based active material as a high-capacity material is used to manufacture a high-capacity battery, the performance of the silicon-based active material as a non-conductive material can be maintained. In this case, the above conductivity range is the most important factor when using the silicon-based negative electrode and is derived based on the porosity of the lithium secondary battery negative electrode after rolling and the dispersion degree of the conductive material.
[0045] In an exemplary embodiment of the present application, there is provided the negative electrode for a lithium secondary battery, wherein the silicon-based active material may include one or more selected from the group consisting of SiOx (x = 0), SiOx (0 < x < 2), SiC, and Si alloys.
[0046] The silicon-based active material may be SiOx, Si / C, or Si. SiOx may include a compound represented by SiOx (0 ≤ x < 2). Since SiO2 does not react with lithium ions and cannot store lithium, x is preferably within the above range. The silicon-based active material may be Si / C composed of a composite of Si and C, or may be Si. In addition, two or more of the above silicon-based active materials may be mixed and used. The negative electrode active material may further include a carbon-based active material and the above silicon-based active material. The carbon-based active material may contribute to improving the cycle characteristics or battery life performance of the negative electrode or secondary battery of the present invention.
[0047] Generally, it is known that the capacity of the silicon-based active material is 10 times that of the carbon-based active material. Therefore, when the silicon-based active material is applied to the negative electrode, it is expected that an electrode with a high energy density level can be achieved even when the thickness is thin.
[0048] In an exemplary embodiment of the present application, the silicon-based active material may include one or more selected from the group consisting of SiOx (x = 0) and SiOx (0 < x < 2), and based on 100 parts by weight of the silicon-based active material, it may include 70 parts by weight or more of SiOx (x = 0).
[0049] In another exemplary embodiment, based on 100 parts by weight of the silicon-based active material, the silicon-based active material may include 70 parts by weight or more, preferably 80 parts by weight or more, more preferably 90 parts by weight or more and 100 parts by weight or less, preferably 99 parts by weight or less, more preferably 95 parts by weight or less of SiOx (x = 0).
[0050] Based on 100 parts by weight of the silicon-based active material, the silicon-based active material according to the present application contains 70 parts by weight or more of SiOx (x = 0). When compared with a silicon-based active material using a SiOx (0 < x < 2) - based active material as the main material, its theoretical capacity is much lower than that of the silicon-based active material of the present application. That is, if a SiOx (0 < x < 2) - based active material is used, it is impossible to achieve conditions equivalent to the charge and discharge capacity of the silicon-based active material of the present invention even if the active material itself is treated in any way.
[0051] In an exemplary embodiment of the present application, pure silicon (Si) can be used as the silicon-based active material. Using pure silicon (Si) as the silicon-based active material can mean that, based on 100 parts by weight of all the silicon-based active materials as described above, pure Si particles (SiOx (x = 0)) not combined with other particles or elements are included within the above range.
[0052] The capacity of the silicon-based active material is significantly higher than that of the commonly used graphite-based active material, leading to more attempts to apply it. However, the volume expansion rate of the silicon-based active material during the charge / discharge process is very high, resulting in only a small amount of the silicon-based active material being mixed with and used in the graphite-based active material.
[0053] Therefore, the present invention has the following characteristics: while using a high content of the silicon-based active material as the negative electrode active material to improve the capacity performance, a binder under specific conditions is used to solve the problems of maintaining the conduction path and the binding of the conductive material, binder, and active material caused by the above-mentioned volume expansion.
[0054] Note that the average particle size (D50) of the silicon-based active material of the present invention can be 5 μm to 10 μm, specifically 5.5 μm to 8 μm, and more specifically 6 μm to 7 μm. When the average particle size is within the above range, the specific surface area of the particles is within a suitable range, such that the viscosity of the negative electrode slurry is formed within a suitable range. Therefore, the particles constituting the negative electrode slurry are smoothly dispersed. In addition, when the size of the silicon-based active material has a value equal to or greater than the lower limit value of the above range, due to the composite made of the conductive material and the binder in the negative electrode slurry, the contact area between the silicon particles and the conductive material is excellent, thereby increasing the possibility of maintaining the conductive network and resulting in an increased capacity retention rate. Note that when the average particle size meets the above range, overly large silicon particles are excluded, making the surface of the negative electrode smooth. Therefore, the phenomenon of uneven current density during charge and discharge can be prevented.
[0055] In an exemplary embodiment of the present application, the silicon-based active material generally has a specific BET specific surface area. The BET specific surface area of the silicon-based active material is preferably 0.01 m 2 / g to 150.0 m 2 / g, more preferably 0.1 m 2 / g to 100.0 m 2 / g, particularly preferably 0.2 m 2 / g to 80.0 m 2 / g, most preferably 0.2 mm 2 / g to 18.0 m 2 The BET specific surface area is measured according to DIN 66131 (using nitrogen).
[0056] In an exemplary embodiment of the present application, the silicon-based active material may be present, for example, in a crystalline or amorphous form, and is preferably not porous. The silicon particles are preferably spherical or fragmentary particles. Alternatively, but less preferably, the silicon particles may also have a fibrous structure, or may be present in the form of a silicon-containing film or coating.
[0057] In an exemplary embodiment of the present application, the content of the silicon-based active material may be 60 parts by weight or more based on 100 parts by weight of the negative electrode active material layer composition.
[0058] In another exemplary embodiment, based on 100 parts by weight of the negative electrode active material layer composition, 60 parts by weight or more, preferably 65 parts by weight or more, more preferably 70 parts by weight or more and 95 parts by weight or less, preferably 90 parts by weight or less, more preferably 85 parts by weight or less of the silicon-based active material may be included.
[0059] Even if the silicon-based active material having a significantly high capacity is used within the above range, the negative electrode composition according to the present application uses a specific conductive material and a binder capable of controlling the volume expansion rate during charge and discharge. Therefore, even if the silicon-based active material is within the above range, the negative electrode composition does not reduce the performance of the negative electrode and has excellent output characteristics during charge and discharge.
[0060] In an exemplary embodiment of the present application, the silicon-based active material may have a non-spherical shape, and the sphericity (circularity) thereof is, for example, 0.9 or less, for example, 0.7 to 0.9, for example, 0.8 to 0.9, and for example, 0.85 to 0.9.
[0061] In the present application, the circularity is determined by the following formula 1-1, where A' is the area and P is the perimeter of the boundary line.
[0062] [Formula 1-1]
[0063] 4πA / P 2
[0064] In the related art, only graphite compounds are generally used as negative electrode active materials. However, in recent years, as the demand for high-capacity batteries has increased, attempts to mix and use silicon-based compounds have also increased in order to increase capacity. However, in the case of silicon-based compounds, even when the properties of the silicon-based active material itself are adjusted as described above according to the present application, the volume may expand rapidly during charging / discharging, resulting in some problems of damaging the conductive path formed in the negative electrode active material layer.
[0065] Therefore, in an exemplary embodiment of the present application, a negative electrode for a lithium secondary battery is provided, wherein the negative electrode active material layer composition further comprises a negative electrode conductive material and a negative electrode binder, and based on 100 parts by weight of the negative electrode active material layer composition, the content of the negative electrode conductive material is greater than 1 part by weight and less than 40 parts by weight.
[0066] In an exemplary embodiment of the present application, the negative electrode conductive material may include one or more selected from the group consisting of a point-shaped conductive material, a surface-shaped conductive material, and a line-shaped conductive material.
[0067] In an exemplary embodiment of the present application, the point-shaped conductive material refers to a point-shaped or spherical conductive material that can be used to improve the conductivity of the negative electrode, has conductivity without causing chemical changes. Specifically, the point-shaped conductive material can be one or more selected from the group consisting of natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, conductive fiber, fluorocarbon, aluminum powder, nickel powder, zinc oxide, potassium titanate, titanium oxide and polyphenylene derivatives, and preferably contains carbon black in terms of high conductivity and excellent dispersibility.
[0068] In an exemplary embodiment of the present application, the dot-shaped conductive material may have a diameter of 40 m 2 / g and above 70 m 2 / g or less, preferably 45 m 2 / g and above 65 m 2 / g or less, more preferably 50 m 2 / g or less and 60 m 2 / g or less BET specific surface area.
[0069] In an exemplary embodiment of the present application, the content of the functional group (volatile substance) of the dot-shaped conductive material may satisfy the range of 0.01% to 1%, preferably 0.01% to 0.3%, and more preferably 0.01% to 0.1%.
[0070] In particular, when the content of the functional group of the dot-shaped conductive material satisfies the above range, the functional group exists on the surface of the dot-shaped conductive material, so that when water is used as a solvent, the dot-shaped conductive material can be smoothly dispersed in the solvent. In particular, in the present invention, due to the use of silicon particles and a specific binder, the content of the functional group of the dot-shaped conductive material can be reduced, which shows an excellent effect on improving dispersibility.
[0071] In an exemplary embodiment of the present application, the content of the functional group may be adjusted according to the degree of heat treatment of the dot-shaped conductive material.
[0072] In an exemplary embodiment of the present application, the particle size of the dot-shaped conductive material may be 10 nm to 100 nm, preferably 20 nm to 90 nm, and more preferably 20 nm to 60 nm.
[0073] In an exemplary embodiment of the present application, the negative electrode conductive material may include a planar conductive material.
[0074] The planar conductive material improves conductivity by increasing the surface contact between silicon particles in the negative electrode, and can be used to suppress disconnection of the conductive path due to volume expansion. The planar conductive material can be expressed as a plate-shaped conductive material or a bulk conductive material.
[0075] In an exemplary embodiment of the present application, the planar conductive material may be provided in the form of being bonded to the surface of the silicon-based particles. Specifically, the planar conductive material may be provided in the form of -OH groups or -O on the surface of the silicon-based particles bonding to the hydrophilic groups of the planar conductive material.
[0076] In an exemplary embodiment of the present application, the planar conductive material may include one or more selected from the group consisting of plate-like graphite, graphene, graphene oxide, and graphite flakes, and may preferably be plate-like graphite.
[0077] In an exemplary embodiment of the present application, the average particle size (D50) of the planar conductive material may be 2 μm to 7 μm, specifically 3 μm to 6 μm, and more specifically 3.5 μm to 5 μm. When the above range is met, sufficient particle size leads to easy dispersion without excessive increase in viscosity of the negative electrode slurry. Therefore, when the same equipment and time are used for dispersion, the dispersion effect is excellent.
[0078] In an exemplary embodiment of the present application, a negative electrode composition is provided, wherein the planar conductive material has a D10 of 0.5 μm or more and 2.0 μm or less, a D50 of 2.5 μm or more and 3.5 μm or less, and a D90 of 6.5 μm or more and 15.0 μm or less.
[0079] In an exemplary embodiment of the present application, as the planar conductive material, a planar conductive material with a high specific surface area having a high BET specific surface area or a planar conductive material with a low specific surface area may be used.
[0080] In an exemplary embodiment of the present application, for the planar conductive material, a planar conductive material with a high specific surface area or a planar conductive material with a low specific surface area can be used without limitation. However, in particular, the planar conductive material according to the present application may be affected to a certain extent by the dispersion effect in terms of electrode performance, and therefore it is particularly preferred to use a planar conductive material with a low specific surface area that does not cause dispersion problems.
[0081] In an exemplary embodiment of the present application, the planar conductive material may have a size of 1 m 2 / g or more BET specific surface area.
[0082] In another exemplary embodiment, the planar conductive material may have a size of 1 m 2 / g and above 500 m 2 / g or less, preferably 5 m 2 / g and above 300 m 2 / g or less, more preferably 5 mm 2 / g and above 250 m 2 / g or less BET specific surface area.
[0083] For the planar conductive material of the present application, a planar conductive material having a high specific surface area or a flat conductive material having a low specific surface area can be used.
[0084] In another exemplary embodiment, the planar conductive material is a planar conductive material having a high specific surface area, and the BET specific surface area may satisfy 50 m 2 / g and above 500 m 2 / g or less, preferably 80 m 2 / g and above 300 m 2 / g or less, more preferably 100 m 2 / g and above 300 m 2 / g or less.
[0085] In another exemplary embodiment, the planar conductive material is a planar conductive material having a low specific surface area, and the BET specific surface area may satisfy 1 m 2 / g and above 40 m 2 / g or less, preferably 5 m 2 / g and above 30 m 2 / g or less, more preferably 5 m 2 / g and above 25 m 2 / g or less.
[0086] Other conductive materials may include linear conductive materials, such as carbon nanotubes. The carbon nanotubes may be bundle-type carbon nanotubes. The bundle-type carbon nanotubes may include a plurality of carbon nanotube units. Specifically, unless otherwise specified, the term "bundle-type" herein refers to a bundle-like or rope-like secondary shape, in which a plurality of carbon nanotube units are arranged side by side with the longitudinal axes of the carbon nanotube units being substantially the same or entangled in an orientation. The carbon nanotube unit comprises a cylindrical graphite sheet having a nanometer-sized diameter and having an sp2 bonding structure. In this case, the properties of a conductor or semiconductor may be expressed depending on the rolling angle and structure of the graphite sheet. Compared with entangled carbon nanotubes, bundle-type carbon nanotubes may be more evenly dispersed during the manufacture of the negative electrode, and a conductive network may be formed more smoothly in the negative electrode to improve the conductivity of the negative electrode.
[0087] In an exemplary embodiment of the present application, the negative electrode conductive material may include a linear conductive material, and the linear conductive material may include SWCNT and MWCNT.
[0088] Illustratively, the linear conductive material may be a single-walled carbon nanotube (SWCNT) having a large BET specific surface area, a linear form, a very small diameter, and a very long length. The linear conductive material such as SWCNT will not be stretched by dispersion, and has a strong ability to recover to its original form when dried. Therefore, the linear conductive material such as SWCNT has a strong ability to recover to its original form when dried, so it is usually present in the form of wrapping or connecting the negative electrode active material or secondary agglomerates. The bonding method may be adsorption by van der Waals forces.
[0089] In an exemplary embodiment of the present application, a negative electrode composition is provided, wherein a content of the negative electrode conductive material is 1 part by weight or more and 40 parts by weight or less based on 100 parts by weight of the negative electrode composition.
[0090] In another exemplary embodiment, the negative electrode conductive material may be contained in an amount of 1 part by weight or more and 40 parts by weight or less, preferably 3 parts by weight or more and 30 parts by weight or less, and more preferably 3% by weight or more and 25 parts by weight or less, based on 100 parts by weight of the negative electrode composition.
[0091] In an exemplary embodiment of the present application, a negative electrode for a lithium secondary battery is provided, wherein the negative electrode conductive material is composed of a planar conductive material and a linear conductive material.
[0092] In an exemplary embodiment of the present application, the negative electrode conductive material may include 80 parts by weight or more and 99.9 parts by weight or less of the planar conductive material and 0.1 parts by weight or more and 20 parts by weight or less of the linear conductive material, based on 100 parts by weight of the negative electrode conductive material.
[0093] In another exemplary embodiment, the negative electrode conductive material may include 80 parts by weight or more and 99.9 parts by weight or less, preferably 85 parts by weight or more and 99.9 parts by weight or less, and more preferably 95 parts by weight or more and 98 parts by weight or less of the planar conductive material, based on 100 parts by weight of the negative electrode conductive material.
[0094] In another exemplary embodiment, the negative electrode conductive material may include 0.1 parts by weight or more and 20 parts by weight or less, preferably 0.1 parts by weight or more and 15 parts by weight or less, and more preferably 1 part by weight or more and 5 parts by weight or less of the linear conductive material, based on 100 parts by weight of the negative electrode conductive material.
[0095] In an exemplary embodiment of the present application, the negative electrode conductive material comprises the planar conductive material and the linear conductive material, and respectively satisfies the above-mentioned composition and proportion, so the life characteristics of the existing lithium secondary battery are not significantly affected, and in particular, when the planar conductive material and the linear conductive material are included, the number of points that can be charged and discharged is increased, so that the output characteristics at a high C rate are excellent, and the amount of gas generated at a high temperature is reduced.
[0096] In an exemplary embodiment of the present application, the negative electrode for a lithium secondary battery is provided, wherein the negative electrode conductive material alone includes the linear conductive material, and the content of the linear conductive material is 5 parts by weight or less based on 100 parts by weight of the negative electrode conductive material.
[0097] In another exemplary embodiment, the negative electrode conductive material may include a linear conductive material alone, and the content of the linear conductive material may be 5 parts by weight or less, preferably 4 parts by weight or less and 0.1 parts by weight or more, preferably 0.5 parts by weight or more, based on 100 parts by weight of the negative electrode conductive material.
[0098] In an exemplary embodiment of the present application, there is provided the negative electrode for a lithium secondary battery, wherein the negative electrode conductive material includes a negative electrode conductive material pre-dispersion liquid, and the negative electrode conductive material pre-dispersion liquid has a viscosity of 2,000 cP or more and 10,000 cP or less.
[0099] That is, the fact that the negative electrode conductive material contains the negative electrode conductive material pre-dispersion liquid means that the negative electrode conductive material is not contained in the negative electrode active material layer composition as it is, but is contained in a pre-dispersed state, and when the viscosity of the negative electrode conductive material pre-dispersion solution in the pre-dispersed state satisfies 2,000 cP or more and 10,000 cP or less and satisfies the following rolling porosity, the negative electrode conductivity according to the present application can be satisfied.
[0100] The negative electrode conductive material according to the present application has a completely different configuration from that of the positive electrode conductive material applied to the positive electrode. That is, the negative electrode conductive material according to the present application is used to maintain contact between the silicon-based active material (the electrode volume expansion of the silicon-based active material is very large due to charging and discharging), and the positive electrode conductive material is used to impart some conductivity while serving as a buffer during rolling, and is completely different from the negative electrode conductive material of the present invention in terms of configuration and function.
[0101] In addition, the negative electrode conductive material according to the present application is applied to the silicon-based active material and has a completely different configuration from the conductive material applied to the graphite-based active material. That is, since the conductive material used for the electrode with the graphite-based active material has only smaller particles than the active material, the conductive material has the characteristics of improving output characteristics and imparting some conductivity, and is completely different in configuration and action from the negative electrode conductive material applied together with the silicon-based active material as in the present invention.
[0102] In an exemplary embodiment of the present application, the planar conductive material used as the above-mentioned negative electrode conductive material has a structure and function different from the structure and function of the carbon-based active material generally used as the negative electrode active material. Specifically, the carbon-based active material used as the negative electrode active material may be artificial graphite or natural graphite, and refers to a material that is processed into a spherical or dot-like shape and is used to facilitate the storage and release of lithium ions.
[0103] On the other hand, the planar conductive material used as the negative electrode conductive material is a material having a planar or plate-like shape, and can be represented by plate-like graphite. That is, the planar conductive material is a material contained in order to maintain a conductive path in the negative electrode active material layer, and refers to a material for ensuring a planar conductive path inside the negative electrode active material layer, rather than playing a role in storing or releasing lithium.
[0104] That is, in the present application, using plate-like graphite as a conductive material means processing graphite into a planar or plate-like shape and using it as a material for ensuring a conductive path, rather than playing a role in storing or releasing lithium. In this case, the negative electrode active material contained together has high capacity characteristics in storing and releasing lithium, and is used to store and release all lithium ions transferred from the positive electrode.
[0105] On the other hand, in the present application, using a carbon-based active material as an active material means that the carbon-based active material is processed into a dot-like or spherical shape and used as a material for storing or releasing lithium.
[0106] In an exemplary embodiment of the present application, the negative electrode binder may include at least one selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene propylene diene monomer rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, polyacrylic acid, and the like in which hydrogen is replaced by Li, Na, Ca, etc., and may also include various copolymers thereof.
[0107] The negative electrode binder according to an exemplary embodiment of the present application is used to retain the active material and the conductive material, thereby preventing the distortion and structural deformation of the negative electrode structure when the volume of the silicon-based active material expands and relaxes. When such a role is met, all general-purpose binders can be applied. Specifically, an aqueous binder can be used, and more specifically, a PAM-based binder can be used.
[0108] In an exemplary embodiment of the present application, the negative electrode for a lithium secondary battery is provided, wherein the negative electrode binder includes an aqueous binder, and the content of the negative electrode binder is 5 parts by weight or more and 30 parts by weight or less based on 100 parts by weight of the negative electrode active material layer composition.
[0109] In another exemplary embodiment, the negative electrode binder may be included in an amount of 5 parts by weight or more and 30 parts by weight or less, preferably 7 parts by weight or more and 15 parts by weight or less, and more preferably 9 parts by weight or more and 12 parts by weight or less, based on 100 parts by weight of the negative electrode active material layer composition.
[0110] In an exemplary embodiment of the present application, the content of the negative electrode binder may be 3 parts by weight or more and 10 parts by weight or less, based on 100 parts by weight of the silicon-based active material.
[0111] In another exemplary embodiment, the negative electrode binder may be contained in an amount of 3 parts by weight or more and 10 parts by weight or less, preferably 3.5 parts by weight or more and 9.5 parts by weight or less, and more preferably 4 parts by weight or more and 9 parts by weight or less, based on 100 parts by weight of the silicon-based active material.
[0112] In the negative electrode for lithium secondary battery according to the present application, in order to maximize the capacity characteristics, the silicon-based active material is used within the above-mentioned weight range, and the volume expansion during charging and discharging is greater than that in the case where a conventional carbon-based active material is used as a main active material. Therefore, the negative electrode contains the negative electrode binder in the above-mentioned content, and thus has the characteristic of effectively controlling the volume expansion caused by charging and discharging of the silicon-based active material having high rigidity.
[0113] In particular, the negative electrode for lithium secondary battery according to the present application satisfies a certain conductivity, and the conductivity can be adjusted by the negative electrode conductive material and the negative electrode binder. The negative electrode conductive material is a conductive material, and the silicon-based active material and the negative electrode binder are non-conductive materials, so by adjusting the proportion and dispersion degree in the electrode in which they are mixed to control the mixing state, the above conductivity can be met. When the conductivity is met, the performance of the silicon-based active material can be maintained.
[0114] Figure 1 1 is a view showing a stacked structure of a negative electrode for a lithium secondary battery according to an exemplary embodiment of the present application. Specifically, a negative electrode 100 for a lithium secondary battery can be seen, which includes a negative electrode active material layer 20 on one surface of a negative electrode collector layer 10 .
[0115] Figure 2 The stack structure of the negative electrode for a lithium secondary battery according to another exemplary embodiment of the present application is shown. Specifically, the negative electrode 100 for a lithium secondary battery including the negative electrode active material layer 20 on both surfaces of the negative electrode collector layer 10 can be seen.
[0116] In the present application, there is a type in which one surface of the negative electrode current collector layer is coated with the negative electrode active material layer (reference Figure 1) and a type in which both surfaces of the negative electrode current collector layer are coated with a negative electrode active material layer (reference Figure 2 ). In this case, the compositions of the negative electrode active material layers coated on both surfaces may be the same or different.
[0117] In an exemplary embodiment of the present application, when the negative electrode active material layer is coated on two surfaces, a negative electrode active material layer comprising the negative electrode composition according to the present application can be used without limitation as long as it is coated on any one of the two surfaces, and a silicon-based negative electrode active material or a carbon-based negative electrode active material that can be generally included can be included on the other surface.
[0118] In an exemplary embodiment of the present application, a negative electrode slurry including the negative electrode active material layer composition may be coated on one surface or both surfaces of a current collector to form a negative electrode for a lithium secondary battery.
[0119] In an exemplary embodiment of the present application, the negative electrode slurry may include a negative electrode active material layer composition and a slurry solvent.
[0120] In an exemplary embodiment of the present application, the solid content of the negative electrode slurry may satisfy a range of 5% to 40%.
[0121] In another exemplary embodiment, the solid content of the negative electrode slurry may satisfy a range of 5% to 40%, preferably 7% to 35%, and more preferably 10% to 30%.
[0122] The solid content of the negative electrode slurry may mean the content of the negative electrode active material layer composition contained in the negative electrode slurry, and may mean the content of the negative electrode active material layer composition based on 100 parts by weight of the negative electrode slurry.
[0123] When the solid content of the negative electrode slurry satisfies the above range, the viscosity is appropriate during the formation of the negative electrode active material layer, thereby minimizing the aggregation of particles of the negative electrode composition to effectively form the negative electrode active material layer.
[0124] In an exemplary embodiment of the present application, the negative electrode collector layer generally has a thickness of 1 μm to 100 μm. Such a negative electrode collector layer is not particularly limited as long as it has high conductivity and does not cause chemical changes in the battery. For example, copper, stainless steel, aluminum, nickel, titanium, fired carbon, copper or stainless steel each surface-treated with carbon, nickel, peptide, silver, etc., aluminum-cadmium alloy, etc. can be used. In addition, the negative electrode collector layer may have fine concave-convex formed on the surface to enhance the binding force of the negative electrode active material, and may be used in various forms such as films, sheets, foils, nets, porous bodies, foams, or non-woven fabrics.
[0125] In an exemplary embodiment of the present application, there is provided the negative electrode for a lithium secondary battery, wherein the thickness of the negative electrode current collector layer is 1 μm or more and 100 μm or less, and the thickness of the negative electrode active material layer is 20 μm or more and 500 μm or less.
[0126] However, the thickness may be variously modified depending on the type and purpose of the negative electrode used, and is not limited thereto.
[0127] In an exemplary embodiment of the present application, the porosity of the negative electrode active material layer may satisfy a range of 10% to 50%.
[0128] In another exemplary embodiment, the porosity of the negative electrode active material layer may satisfy a range of 10% to 40% both inclusive, preferably 20% to 40% both inclusive, and more preferably 30% to 40% both inclusive.
[0129] The porosity varies depending on the composition and content of the silicon-based active material, the conductive material and the binder contained in the negative electrode active material layer, and in particular, when the silicon-based active material and the conductive material are contained in a specific composition and content according to the present application, the above range is satisfied so that the electrode has conductivity and resistance within an appropriate range.
[0130] An exemplary embodiment of the present application provides a lithium secondary battery including: a positive electrode; a negative electrode for a lithium secondary battery according to the present application; a separator disposed between the positive electrode and the negative electrode; and an electrolyte.
[0131] Figure 31 is a view showing a stacking structure of a lithium secondary battery according to an exemplary embodiment of the present application. Specifically, a negative electrode 100 for a lithium secondary battery including a negative electrode active material layer 20 on one surface of a negative electrode collector layer 10 can be seen, a positive electrode 200 for a lithium secondary battery including a positive electrode active material layer 40 on one surface of a positive electrode collector layer 50 can be seen, and the negative electrode 100 for a lithium secondary battery and the positive electrode 200 for a lithium secondary battery are formed in a stacking structure with a separator 30 interposed therebetween. In addition, the negative electrode active material layer 20 may be formed on both surfaces of the negative electrode collector layer 10. In addition, the positive electrode active material layer 40 may be formed on both surfaces of the positive electrode collector layer 50.
[0132] A secondary battery according to an exemplary embodiment of the present specification may particularly include the above-mentioned negative electrode for lithium secondary batteries. Specifically, the secondary battery may include a negative electrode, a positive electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte, and the negative electrode is the same as the above-mentioned negative electrode. Since the negative electrode has been described above, its detailed description is omitted.
[0133] The positive electrode may include a positive electrode collector and a positive electrode active material layer formed on the positive electrode collector and including the positive electrode active material.
[0134] In the positive electrode, the positive electrode collector is not particularly limited as long as it has conductivity and does not cause chemical changes in the battery. For example, stainless steel, aluminum, nickel, titanium, fired carbon, aluminum or stainless steel each surface-treated with carbon, nickel, titanium, silver, etc., and the like can be used. In addition, the positive electrode collector can generally have a thickness of 3 μm to 500 μm, and the surface of the collector can be formed with fine concave-convex to enhance the adhesion of the positive electrode active material. For example, the positive electrode collector can be used in various forms such as films, sheets, foils, nets, porous bodies, foams, and non-woven fabrics.
[0135] The positive electrode active material may be a commonly used positive electrode active material. Specifically, the positive electrode active material may be a layered compound such as lithium cobalt oxide (LiCoO2) and lithium nickel oxide (LiNiO2), or a compound substituted with one or more transition metals; lithium iron oxide such as LiFe3O4; lithium manganese oxide such as Li 1+c1 Mn 2-c1 O4 (0≤c1≤0.33), LiMnO3, LiMn2O3 and LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, V2O5 and Cu2V2O7; 1-c2 M c2Ni-site lithium nickel oxide represented by the chemical formula LiMn 2- C3 A lithium manganese composite oxide represented by MnO2 (wherein M is at least one selected from the group consisting of Co, Ni, Fe, Cr, Zn and Ta, and satisfies 0.01≤c3≤0.1) or Li2Mn3MO8 (wherein M is at least one selected from the group consisting of Fe, Co, Ni, Cu and Zn); LiMn2O4 in which a portion of Li in the chemical formula is replaced by an alkaline earth metal ion; and the like, but not limited thereto. The positive electrode may be a Li metal.
[0136] The positive electrode active material layer may include a positive electrode conductive material and a positive electrode binder as well as the positive electrode active material.
[0137] In this case, the positive electrode conductive material is used to impart conductivity to the electrode, and can be used without particular limitation, as long as the positive electrode conductive material has electronic conductivity without causing chemical changes in the battery to be constructed. Specific examples may include: graphite, such as natural graphite and artificial graphite; carbon-based materials, such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powder or metal fiber, such as copper, nickel, aluminum, and silver; conductive whiskers, such as zinc oxide and potassium titanate; conductive metal oxides, such as titanium oxide; or conductive polymers, such as polyphenylene derivatives; and the like, and any one of them or a mixture of two or more of them may be used.
[0138] In addition, the positive electrode binder is used to improve the bonding between the positive electrode active material particles and the adhesion between the positive electrode active material and the positive electrode collector. Specific examples may include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber or its various copolymers, and any one of them or a mixture of two or more of them can be used.
[0139] The separator is used to separate the negative electrode and the positive electrode, and to provide a migration path for lithium ions, wherein any separator can be used as a separator without particular limitation, as long as it is commonly used in secondary batteries, and in particular, it is preferred to use a separator having high moisture retention capacity for electrolytes and low resistance to the migration of electrolyte ions. Specifically, a porous polymer film can be used, for example, a porous polymer film made of a polyolefin-based polymer, such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminated structure having two or more layers thereof. In addition, a common porous nonwoven fabric can be used, for example, a nonwoven fabric formed of a high melting point glass fiber, a polyethylene terephthalate fiber, etc. In addition, a coated separator comprising a ceramic component or a polymer material can be used to ensure heat resistance or mechanical strength, and a separator having a monolayer or multilayer structure can be selectively used.
[0140] Examples of the electrolyte may include an organic liquid electrolyte, an inorganic liquid electrolyte, a solid polymer electrolyte, a gel-type polymer electrolyte, a solid inorganic electrolyte, or a molten-type inorganic electrolyte that may be used to manufacture the lithium secondary battery, but are not limited thereto.
[0141] Specifically, the electrolyte may include a non-aqueous organic solvent and a metal salt.
[0142] As the non-aqueous organic solvent, for example, an aprotic organic solvent such as N-methyl-2-pyrrolidone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, triester phosphate, trimethoxymethane, dioxolane derivatives, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate or ethyl propionate can be used.
[0143] Especially, among the carbonate-based organic solvents, ethylene carbonate and propylene carbonate as cyclic carbonates are high viscosity organic solvents, and can be preferably used because they have high dielectric constants to dissociate lithium salts well. When the cyclic carbonates are mixed with linear carbonates (such as dimethyl carbonate and diethyl carbonate) with low viscosity and low dielectric constant in a suitable ratio and used, an electrolyte with high conductivity can be prepared, so such a combination can be more preferred.
[0144] A lithium salt may be used as the metal salt, and the lithium salt is a material that is easily soluble in a non-aqueous electrolyte, wherein, for example, a lithium salt selected from F - , Cl- ,I - 、NO3 - 、N(CN)2 - 、BF4 - 、ClO4 - PF6 - 、(CF3)2PF4 - 、(CF3)3PF3 - 、(CF3)4PF2 - 、(CF3)5PF - 、(CF3)6P - CF3SO3 - CF3CF2SO3 - 、(CF3SO2)2N - 、(FSO2)2N - CF3CF2(CF3)2CO - 、(CF3SO2)2CH - 、(SF5)3C - 、(CF3SO2)3C - CF3(CF2)7SO3 - CF3CO2 - 、CH3CO2 - 、SCN - and (CF3CF2SO2)2N - One or more of the composed group may be used as the anion of the lithium salt.
[0145] In addition to the above electrolyte components, one or more additives, for example, halogenated alkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, (condensed) glycol dimethyl ethers, hexamethylphosphoric triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted Oxazolidinone, N,N-substituted imidazolidine, ethylene glycol dialkyl ether, ammonium salt, pyrrole, 2-methoxyethanol or aluminum chloride may be further included in the electrolyte for the purpose of improving the life characteristics of the battery, inhibiting the reduction of the battery capacity, improving the discharge capacity of the battery, etc.
[0146] An exemplary embodiment of the present invention provides a battery module including the secondary battery as a unit cell and a battery pack including the secondary battery. Since the battery module and the battery pack include the secondary battery having high capacity, high rate performance and high cycle characteristics, the battery module and the battery pack can be used as a power source for medium and large devices selected from electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles and power storage systems.
[0147] Example
[0148] Hereinafter, preferred embodiments will be provided to better understand the present invention. It will be apparent to those skilled in the art that these embodiments are provided merely to illustrate the present invention, and various modifications and changes may be made within the scope and technical spirit of the present invention. Such modifications and changes naturally fall within the scope of the claims contained herein.
[0149] <Preparation Example>
[0150] <Example 1>
[0151] Si (average particle size (D50): 3.5 μm) used as a silicon-based active material, a first conductive material, a second conductive material, and polyacrylamide used as a binder were added to distilled water used as a solvent for forming a negative electrode slurry in a weight ratio of 88:2.6:0.4:9 to prepare a negative electrode slurry (solid concentration: 25 wt %).
[0152] The first conductive material is SWCNT and has a thickness of about 1000 to 1500 m 2 / g BET specific surface area and aspect ratio of more than 10000 (specific surface area: 58 m 2 / g, diameter: 37 nm, volatile matter: 0.01%), the second conductive material is MWCNT.
[0153] In this case, the first conductive material and the second conductive material form a negative electrode conductive material pre-dispersion liquid so that the solid content in water as a dispersion medium is 15%, and the negative electrode pre-dispersion liquid is dispersed by a grinding device using a homogenizer to prepare a negative electrode conductive material pre-dispersion liquid with a viscosity of 6700 cP.
[0154] As a mixing method, the negative electrode conductive material pre-dispersion liquid, a binder, and water were dispersed at 2500 rpm for 30 minutes using a homomixer, the active material was added thereto, and the resulting mixture was dispersed at 2500 rpm for 30 minutes to prepare a slurry.
[0155] The negative electrode slurry was prepared at 85 mg / 25 cm 2 The negative electrode (negative electrode thickness: 41 μm) was prepared by coating the negative electrode active material layer with a loading amount of 200 μm on both surfaces of a copper current collector (thickness: 8 μm) used as a negative electrode current collector, which was then rolled and dried in a vacuum oven at 130°C for 10 hours to form the negative electrode active material layer (thickness: 33 μm). In this case, the porosity and conductivity of the negative electrode active material layer are shown in Table 1 below.
[0156]
[0157] <Preparation of Secondary Battery>
[0158] By using LiNi as the positive electrode active material 0.6 Co 0.2 Mn 0.2 O2 (average particle size (D50): 15 μm), carbon black (product name: Super C65, manufacturer: Timcal) as a conductive material, and polyvinylidene fluoride (PVdF) as a binder were added to N-methyl-2-pyrrolidone (NMP) as a solvent for forming a positive electrode slurry in a weight ratio of 97:1.5:1.5 to prepare a positive electrode slurry (solid concentration: 78 wt %).
[0159] The positive electrode slurry was prepared at 537 mg / 25 cm 2 The positive electrode was prepared by coating the positive electrode with a loading amount of 77 μm on both surfaces of an aluminum current collector (thickness: 12 μm) used as the positive electrode current collector, and then rolling it and drying it in a vacuum oven at 130°C for 10 hours to form a positive electrode active material layer (thickness: 65 μm), thereby preparing a positive electrode (positive electrode thickness: 77 μm, porosity: 26%).
[0160] The secondary battery of Example 1 was prepared by interposing a polyethylene separator between the positive electrode and the negative electrode of Example 1 and injecting an electrolyte.
[0161] The electrolyte was obtained by adding 3 wt % of vinylene carbonate based on the total weight of the electrolyte to an organic solvent in which fluoroethylene carbonate (FEC) and diethyl carbonate (DEC) were mixed in a volume ratio of 30:70 and adding LiPF6 as a lithium salt to a concentration of 1 M.
[0162] Each secondary battery was prepared in the same manner as the above method except that the negative electrodes of Examples and Comparative Examples were used.
[0163] Experimental Example 1: Evaluation of Single Battery Life
[0164] For the secondary batteries prepared in the examples and comparative examples, an electrochemical charging and discharging device was used to evaluate the life span and capacity retention rate. The secondary batteries were charged and discharged under the following conditions:
[0165] 1) First cycle: charge (0.33C CC / CV charge, 4.2 V, 0.05C cut-off) and discharge (0.33C CC discharge, 3.0 V cut-off), and
[0166] 2) Second cycle: charge (1.0C CC / CV charge, 4.2 V, 0.05C cut-off) and discharge (0.5C CC discharge, 3.0 V cut-off).
[0167] The capacity retention rate at the Nth cycle was evaluated by the following formula. The results are shown in Table 2 below.
[0168] Capacity retention rate (%) = {(discharge capacity of the Nth cycle) / (discharge capacity of the first cycle)}×100
[0169]
[0170] As can be seen in Tables 1 and 2 above, it can be confirmed that the batteries containing the negative electrodes according to Examples 1 to 4 of the present application satisfy the porosity and dispersion of the conductive material to control the conductivity within the range of the present application, thereby resulting in the characteristics of ensuring and maintaining the performance of the silicon-based active material.
[0171] In the case of Comparative Example 1, the range of the conductivity is lower than the range according to the present application, while in the case of Comparative Example 2, the range is higher than the range according to the present application. Likewise, the porosity and dispersion of the conductive material are adjusted and formed as described above, and in this case, it can be confirmed that the capacity retention rate is reduced, as can be seen in Table 2. Specifically, it can be confirmed that in the case of Comparative Example 1, the conductivity is low and it is not easy to form a conductive network, resulting in poor performance, while in the case of Comparative Example 2, the conductivity range is quite high, which leads to problems in terms of capacity and life.
Claims
1. A negative electrode for a lithium secondary battery, the negative electrode for the lithium secondary battery comprising: A negative electrode current collector layer; and A negative electrode active material layer, the negative electrode active material layer comprising a negative electrode active material layer composition and being provided on one surface or both surfaces of the negative electrode current collector layer, Wherein the negative electrode active material layer composition comprises a silicon-based active material, Wherein the negative electrode active material layer has a porosity of 10% to 50%, and The conductivity of the negative electrode for the lithium secondary battery satisfies 1 S / cm 2 Above and 3,000 S / cm 2 The following range.
2. The negative electrode for a lithium secondary battery according to claim 1, wherein the silicon-based active material comprises one or more selected from the group consisting of SiOx (x = 0), SiOx (0 < x < 2), SiC, and Si alloys.
3. The negative electrode for a lithium secondary battery according to claim 1, wherein the silicon-based active material comprises one or more selected from the group consisting of SiOx (x = 0) and SiOx (0 < x < 2), and Based on 100 parts by weight of the silicon-based active material, the silicon-based active material comprises 70 parts by weight or more of the SiOx (x = 0).
4. The negative electrode for a lithium secondary battery according to claim 1, wherein based on 100 parts by weight of the negative electrode active material layer composition, the content of the silicon-based active material is 60 parts by weight or more.
5. The negative electrode for a lithium secondary battery according to claim 1, wherein the negative electrode active material layer composition further comprises a negative electrode conductive material and a negative electrode binder, and Wherein based on 100 parts by weight of the negative electrode active material layer composition, the content of the negative electrode conductive material is 1 part by weight or more and 40 parts by weight or less.
6. The negative electrode for a lithium secondary battery according to claim 5, wherein the negative electrode conductive material comprises a linear conductive material, and Wherein based on 100 parts by weight of the negative electrode conductive material, the content of the linear conductive material is 5 parts by weight or less.
7. The negative electrode for a lithium secondary battery according to claim 5, wherein the negative electrode conductive material consists of a planar conductive material and a linear conductive material.
8. The negative electrode for a lithium secondary battery according to claim 7, wherein based on 100 parts by weight of the negative electrode conductive material, the negative electrode conductive material comprises 80 parts by weight or more and 99.9 parts by weight or less of the planar conductive material and 0.1 part by weight or more and 20 parts by weight or less of the linear conductive material.
9. The negative electrode for a lithium secondary battery according to claim 5, wherein the negative electrode conductive material comprises a negative electrode conductive material pre-dispersion liquid, and Wherein the viscosity of the negative electrode conductive material pre-dispersion liquid is 2,000 cP or more and 10,000 cP or less.
10. The negative electrode for a lithium secondary battery according to claim 5, wherein based on 100 parts by weight of the negative electrode active material layer composition, the content of the negative electrode binder is 5 parts by weight or more and 30 parts by weight or less.
11. The negative electrode for a lithium secondary battery according to claim 1, wherein the negative electrode current collector layer has a thickness of 1 μm or more and 100 μm or less, and Wherein the negative electrode active material layer has a thickness of 20 μm or more and 500 μm or less.
12. A lithium secondary battery, comprising: positive electrode; The negative electrode for a lithium secondary battery according to any one of claims 1 to 11; a separator disposed between the positive electrode and the negative electrode; and Electrolytes.
Citation Information
Patent Citations
Anode for lithium ion battery
JP2009080971A